Subjugated knowledges, contested spaces and African Christianity: An appraisal - Akesseh, Ebenezer (HTS teologiese studies, 2023)
Religion mediates and shapes how people negotiate and navigate their existential realities. Christianity accentuates the belief in Jesus Christ and prescribes how that belief should influence the worldview and actions of people. One of the challenges of the reception of Christianity in Africa is that African Traditional Religion remains the cosmic lens through which Christians confront their spiritual and ethical dilemmas and choices vis-à-vis the exhortations of the Bible message. This paper examines the force of the Christian message for African Christians. It looks at how the Christian message was presented, how African Christians appropriate the gospel message and how they fill the ‘gaps’ in their practice of Christianity. As movies bring to bear stories about lived realities and shape attitudes and behaviour, this paper also examines the reception of the Biblical message by reviewing a selection of African movies. I argue that Christianity must provide answers to the critical questions and unmet needs essential to Africans. To achieve this would require paying attention to what Michel Foucault describes as the ‘insurrection of subjugated knowledges,’ which take into account naïve knowledges operating at local or regional levels but serve as the local discursivities that amplify how the ‘subjugated knowledges’ influence the reception of the Biblical message in the African cultural matrix.Contribution: This paper reveals the enduring cross-pressures of Africans as they are invited to subjugate their primordial knowledges and practices to the orthodoxy of mainstream Christianity. It cites the examples of neo-Pentecostal and para-Christian enactments as offering possible insights into a need for Christianity to be more responsive and functionally relevant to the African reality. Such an approach resonates with the orientation of HTS Teologiese Studies (HTS) towards scholarship that is discursively dynamic and contextually sensitive to the multilayered contexts, cultures and cosmologies of the African Christian.